Eskimo family sitting beneath upturned umiak, Alaska, ca. 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: Family of King's Island Eskimos living under skin boat. Alaska. Copyright, F.H. Nowell, '04 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number